The Influence of Work Environment And Compensation on The Peformance of Preparation Departement Employess at PT Adis Dimension Footwear Tangerang Regency - Sanur, Shella Permata; Sudinta, Heru; Setiyawan, Temmy (Faculty of Science and Technology University of Pramita Indonesia, 2026)
The Work Environment and Compensation on Employee Performance in the Preparation Division at PT Adis Dimension Footwear, Tangerang Regency.This study employed a quantitative associative method, which aims to analyze cause-and-effect relationships or the influence among two or more variables using numerical data that are statistically analyzed to test hypotheses and to explain a particular phenomenon. The population in this study was all employees in the Preparation Department at PT Adis Dimension Footwear Kabupaten Tangerang. The sample size was 98 respondents. The sampling technique used was simple random sampling. The Slovin formula was used to determine a representative sample size in quantitative research. Data collection techniques included observation, questionnaires, and documentation. Data analysis employed multiple linear regression analysis using SPSS 26. Data validity was verified through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, the work environment significantly influences the performance of Preparation Division employees at PT. Adis Dimension Footwear Kabupaten Tangerang, which is indicated by the calculated t value > t table (4.082>1.985) and a significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, compensation significantly influences the performance of employees in the Preparation section at PT. Adis Dimension Footwear Kabupaten Tangerang, which is indicated by the calculated t value > t table (7.994>1.985) and a significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, the work environment and compensation significantly influence the performance of employees in the Preparation section at PT. Adis Dimension Footwear Kabupaten Tangerang, which is indicated by F count > F table (72.658 >3.09) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that work environment and compensation variables, both partially and simultaneously, have a significant influence on the performance of employees in the Preparation section at PT. Adis Dimension Footwear Kabupaten Tangerang.